2012
DOI: 10.1007/s11030-012-9402-1
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization potential of oligonucleotides comprising 3′-O-methylated altritol nucleosides

Abstract: Abstract:A series of 3'-O-methylated D-altrohexitol nucleoside analogs (MANA) was synthesized comprising all four base moieties, adenine, cytosine, uracil and guanine. These monomers were incorporated into While the specificity of these new synthons is slightly lower compared to mismatches within RNA double strands, it is similar to the discrimination potential of other hexitol modifications (HNA and ANA) which already proved their biologic interest, highlighting the potential of MANA constructs in antisense a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Where the natural RNA duplex displayed a Tm of 40.6 °C, the DMANA construct still paired albeit with slightly lower affinity (−0.3 °C/modification). The different hexitol constructs on the other hand strongly increased the affinity for the RNA complement as documented before [23,34]. It hence can be concluded that the DMANA analogues are different from the previous hexitol series of compounds with a constrained 6-membered ring conformation fit for pairing to RNA.…”
Section: Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…Where the natural RNA duplex displayed a Tm of 40.6 °C, the DMANA construct still paired albeit with slightly lower affinity (−0.3 °C/modification). The different hexitol constructs on the other hand strongly increased the affinity for the RNA complement as documented before [23,34]. It hence can be concluded that the DMANA analogues are different from the previous hexitol series of compounds with a constrained 6-membered ring conformation fit for pairing to RNA.…”
Section: Resultssupporting
confidence: 58%
“…The selective O - vs . N -methylation mainly depends upon the dielectric constant of the solvent [23,25] and the stability of sodium-enolate chelation [26]. Hence, low dielectric constant and high chelation stabilizing capacity of THF afforded a higher O -selectivity compared to DMF.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations